Faktor-Faktor yang Mempengaruhi Kebijakan Dividen pada Perusahaan LQ45 - Asiam, Siti; Rahmawati, Ririn (IAIN Kudus, 2022)
This research aimed to examine the effect of Leverage, Profitability, Liquidity and Company Size on the dividend policy of LQ-45 companies during 2018-2021. Based on the purposive sampling technique, 18 companies were used as research objects and 72 observations. The data was analyzed by panel data regression analysis in the form of a Random Effect Model (REM). The results identified that only profitability variables affect dividend policy, while leverage, liquidity, and company size do not affect dividend policy.